Expecting the Next Coup? The Unchallenged Brazilian Military's Bargaining Power. - Duarte, Érico Esteves (Bulletin of Latin American Research, 2026)
The civil‐military relations in Brazil have faced criticism due to weak political institutions and significant military autonomy, resulting in a regression of democratisation. This article posits that the shortcomings in Brazilian civil‐military relations have historical roots, with military prerogatives established in the early twentieth century and largely unopposed since that time. The military's robust corporate identity and its pivotal role in public administration and policy have granted it significant bargaining power, enabling resistance to reforms and undermining civilian authority. This paper provides evidence indicating that elected Brazilian administrations since 1995, particularly during Silva (2003–2011, 2023–) and Rousseff (2011–2016) administration, have significantly militarised the defence decision‐making process and increased the involvement of the armed forces in public security, infrastructure development and public administration.